Pengaruh Kualitas Produk, Persepsi Harga Dan Iklan Terhadap Keputusan Pembelian Produk Komunikasi: Studi Kasus Pada Handphone Xiaomi Di Kota Bogor - Alfariza, Muhammad; Pratomo, Anton Widio (Jurnal Informatika Kesatuan, 2023)
The purpose of this study was to determine the effect of Product Quality, Price Perseption and Advertising on Purchase Decisions Case study on Xiaomi Mobile Phones in the City of Bogor. The number of samples used in this study amounted to 100 respondents taken from users Xiaomi Mobile Phones. The tool used to collect data is a questionnaire and the data in this study were processed using statistical package For Social Science (SPSS) version 25. The results of the analysis show that (1) Product quality has a positive and significant effect on purchasing decisions with a t-count of 4,252, which is greater than t-table 1.66 and a significant value of 0.000 <0.05. (2) Price Perseption has a positive and significant effect on purchasing decisions with a t-count of 4,832, which is greater than t-table 1.66 and a significance value of 0.000 <0.05. (3) Advertising has a positive and significant effect on purchasing decisions with a t-count of 3,362, which is greater than t-table 1.66 and a significance value of 0.001 <0.05. (4) Product Quality, Price Perseption and Advertising together have a positive and significant relationship to Purchase Decisions with an f-count of 37,108, which is greater than f-table 2.70 and a significance value of 0.000 <0.05. Keywords : Product Quality, Price Perseption and Advertising on Purchase Decisions.